Mangrove Planting Activities as an Effort to Preserve Coastal Ecosystems in Camplong, Sampang Regency - Mohammad Taufiq Shidqi; Mohammad Shoimus Sholeh; Endang Tri Wahyurini; Lia Kristiana; Ardila Rahmawati; Siti Holifah; Yenni Arista Cipta Ekalaturrahmah (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
Mangrove planting on the coast of Camplong, Sampang, is part of an environmental conservation effort carried out by the local community with support from academics and the regional government. This community service activity aims to identify the factors influencing the success of the mangrove planting program and its impacts on coastal ecosystems and the local community. The methods used include field surveys, interviews with relevant stakeholders, and secondary data analysis. The results of the program indicate that factors such as selecting the appropriate mangrove species, active community involvement in maintenance, and policy support from the government significantly influence the success of this program. Observed positive impacts include increased biodiversity, protection against coastal erosion, and enhanced environmental awareness and economic well-being of the local community. However, challenges such as funding limitations and the impacts of climate change require sustainable adaptive strategies for future mangrove management. This community service initiative makes an important contribution to advancing the understanding of the significance of mangrove planting as an effort to preserve coastal areas in Indonesia